Massive Open Online Course (MOOC): our saviour during COVID-19 pandemic?/ Safwana Nur Widad Safri, Zurinawati Mohi and Mohd Hafiz Hanafiah - Safri, Safwana Nur Widad; Mohi, Zurinawati; Hanafiah, Mohd Hafiz (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2020)
When the second wave of COVID-19 hit Malaysia, public and private universities must be closed as to adhere to the government Restriction of Movement Order (RMO). This unprecedented phenomenon has forced the university management to implement a contingency plan of shifting all their academic lessons online. This paper discusses the usage of Massive Open Online Course (MOOC) by the higher institution in Malaysia during COVID-19. This paper concludes that MOOC is proven to be a stable platform and can provide independent and flexibles learning experiences to the higher education students.